Growth and Instability in Pine Rosin Production, Export and Import In India - Prasad, Niranjan (Indian Forester, 2026)
This study examines the growth and instability in India's production, export, and import of pine rosin from 2003–04 to 2023–24. Analysis reveals a severe decline in domestic resin production, particularly in Himachal Pradesh and Uttarakhand, with an overall annual growth rate of –7.326% between 2007–08 and 2019–20. This drop is attributed to ecological stressors, unsustainable tapping practices, socio-economic shifts, and policy constraints. As a result, India's export volumes collapsed by over 86%, becoming highly unstable and marginal, while unit export values rose significantly. Conversely, imports grew steadily at 3.124% per annum, reaching 42,542 tonnes in 2023–24, with over 75% sourced from Indonesia, highlighting heavy import dependence. Instability indices confirm volatile exports but stable imports, underscoring supply-side vulnerabilities. The paper concludes with a forward-looking estimate suggesting that tapping just 5% of India's Pinus roxburghii trees could meet domestic demand, save approximately $47.82 million in imports, and generate significant rural employment. Urgent policy interventions are recommended to revitalize sustainable domestic production and reduce external reliance.